2023
DOI: 10.1097/bpb.0000000000001077
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of assessing proximal femur geometry with Rutz classification schema in patients with cerebral palsy

Abstract: Our investigation aimed to assess the reliability of the femoral head shape classification system devised by Rutz et al. and observe its application in patients with cerebral palsy (CP) at different skeletal maturity levels. Four independent observers assessed anteroposterior radiographs of the hips of 60 patients with hip dysplasia associated with non-ambulatory CP (Gross Motor Function Classification System levels IV and V) and recorded the femoral head shape radiological grading system as described by Rutz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Of note, Rutz et al 30 found that femoral head shape was not an independent predictor of outcome of reconstruction. Recent papers Kasprzyk et al 43 and Ulusaloglu et al 44 report that the grade of femoral head shape was significantly associated with increasing MP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, Rutz et al 30 found that femoral head shape was not an independent predictor of outcome of reconstruction. Recent papers Kasprzyk et al 43 and Ulusaloglu et al 44 report that the grade of femoral head shape was significantly associated with increasing MP.…”
Section: Discussionmentioning
confidence: 99%
“…The Rutz et al 30 classification can be used to classify the shape of the femoral head. Kasprzyk et al 43 reported that while it is reliable (showing moderate-to-substantial intra- and interobserver reliability (mean κ = 0.64 and mean κ = 0.5, respectively)), clinical utility of this classification system is yet to be established in the literature. This radiological classification system was therefore not used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth knowing that the femoral head shape classification system devised by Rutz was recently assessed with moderate to substantial intra-observer reliability and moderate inter-observer reliability. 15 Pain complaints in patients with CP are common with studies suggesting a prevalence of pain up to 74%. [16][17][18] Children with GMFCS level III-V experience hip pain more often than those at level I-II, which is also correlated with hip migration.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth knowing that the femoral head shape classification system devised by Rutz was recently assessed with moderate to substantial intra-observer reliability and moderate inter-observer reliability. 15 …”
Section: Discussionmentioning
confidence: 99%